Effectiveness Of Fertilizer Distribution Policy For Farmers In Sumberbendo Village, Probolinggo District - Khoirril, Oktavia Putri; Novita, Noftarida Dina; Sari, Nova Dwi Nur Kumala; Handoyo, Muhammad Akbar Putra; Manggalou, Singgih (Journal of Governance and Administrative Reform, 2023)
Abstract This research is motivated by the complexity of the distribution system of subsidized and non-subsidized fertilizers to farmers, this research is deemed necessary to be carried out in order to find out how the effectiveness of the distribution of subsidized and non-subsidized fertilizers to farmers or POKTAN (Kelompok Tani-Farmer Groups) through kiosk intermediaries as official agents of fertilizer distributors, especially in Sumberbendo Village, Sumberasih District, Probolinggo Regency. The theory used in this study uses Sutrisno's (2010) effectiveness theory by measuring five indicators, namely Program Understanding, Target Accuracy, Timeliness, Achievement of Goals, and Real Change. This research uses qualitative descriptive research methods. The results in this study can be concluded that the effectiveness of the Fertilizer Distribution Policy for Farmers in Sumberbendo Village, Probolinggo Regency can be said to be less effective. Keywords: distribution policy; fertilizer; subsidies Abstrak Penelitian ini dilatarbelakangi oleh rumitnya sistem pendistribusian pupuk bersubsidi dan non subsidi kepada petani, penelitian ini dirasa perlu untuk dilakukan guna mengetahui bagaimana efektivitas pendistribusian pupuk bersubsidi maupun nonsubsidi kepada para petani atau POKTAN (Kelompok Tani) melalui perantara kios sebagai agen resmi penyalur pupuk khususnya di Desa Sumberbendo Kecamatan Sumberasih Kabupaten Probolinggo. Teori yang digunakan dalam penelitian ini menggunakan teroi efektivitas Sutrisno (2010) dengan mengukur lima indikator yakni Pemahaman Program, Ketepatan Sasaran, Ketepatan Waktu, Tercapainya Tujuan, dan Perubahan Nyata.. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Hasil dalam penelitian ini dapat disimpulkan bahwa Efektivitas Kebijakan Distribusi Pupuk Bagi Petani di Desa Sumberbendo Kabupaten Probolinggo dapat dikatakan kurang efektif. Kata kunci: evaluasi kebijakan distribusi; pupuk; subsidi